Self-Care and Treatment Adherence for Blood Pressure Control among Patients with Hypertension: a Cross-sectional Study - Muhammad Deri Ramadhan; Eny Kusmiran; Istianah Istianah (Institut Kesehatan YARSI Mataram, 2025)
The prevalence of hypertension is increasing every year. The keys of full success in controlling blood pressure among patients with hypertension were self-care and medication adherence. The research problem was that patients with hypertension still had inadequate self-care skills and were not compliant with treatment regimens. The aim of the study was to analyze the association between self-care and medication adherence with blood pressure control among patients with hypertension. The method, design of the study was cross-sectional. Primary data collection was conducted in outpatient wards at Type A Hospital, Bandung-Indonesia with accidental sampling technique. Period of data collection was February-March 2025. Total sample involved 138 respondents. The instruments used in this study were High Blood Pressure-Self-care Profile (HBP-SCP) and Modified-Morisky Adherence Scale-8 (MMAS-8). The statistical test used was Chi-Square. Results: We found 82.0% respondents with low self-care, 86.0% not adhere to medication, and 66.0% respondents with uncontrolled blood pressure. The results of the study showed there was a significant association between self-care and blood pressure control (P < .001), medication adherence and blood pressure control among patients with hypertension (P < .001). Recommendations related to improving self-care and medication adherence need to be evaluated periodically, support from health care professionals through ongoing health education or the use of appropriate technology needs to be carried out to monitor the self-care abilities of hypertension sufferers to avoid various complications. ABSTRAK Prevalensi hipertensi setiap tahunnya meningkat. Kunci keberhasilan pengendalian tekanan darah yaitu kemampuan self-care dan kepatuhan pengobatan. Masalah penelitian masih ditemukan penderita hipertensi yang memiliki kemampuan self-care yang kurang memadai dan tidak patuh terhadap rejimen pengobatan. Tujuan: menganalisis hubungan self-care dan kepatuhan pengobatan dengan pengendalian tekanan darah penderita hipertensi. Metode: desain studi cross sectional. Pengumpulan data primer penderita hipertensi yang rawat jalan di Poli Ginjal dan Hipertensi RS Tipe A Bandung dengan teknik accidental sampling. Periode Februari-Maret 2025. Besar sampel dalam studi 138 responden. Instrumen penelitian High Blood Pressure-Self-care Profile (HBP-SCP) dan Modified-Morisky Adherence Scale-8 (MMAS-8). Uji statistik yang digunakan Chi-Square. Hasil: Terdapat 82.0% responden dengan kemampuan self-care rendah, 86.0% responden dengan kepatuhan pengobatan rendah, dan 66.0% responden dengan tekanan darah tidak terkendali. Hasil studi diperoleh hubungan yang signifikan antara self-care dengan pengendalian tekanan darah pada penderita hipertensi (P < .001) dan kepatuhan pengobatan dengan pengendalian tekanan darah penderita hipertensi (p < .001). Rekomendasi studi terkait peningkatan self-care dan kepatuhan pengobatan perlu dievaluasi secara berkala, dukungan petugas kesehatan melalui pendidikan kesehatan berkelanjutan atau pemanfaat teknologi tepat guna perlu dilakukan untuk memantau kemampuan perawatan diri penderita hipertensi agar terhindar dari berbagai komplikasi.